Syaralise Empire / Nabilah Farhah Adnan ... [et al.] - Adnan, Nabilah Farhah; Mustafa Kamal, Putri Nabila; Mohd Azhan, Azhanis Azreen; Norman, Nurul Atikah; Wan Mohamad Zuki, Wan Nur Jannah (2021)
All Batu Pahat, Johor residents and social media platforms have recognized Syaralise Empire. This is due to a lack of individuals offering a nice pillow that is distinct from a typical pillow and has a choice of pillow designs and pattern to choose from. Syaralise Empire's sell a product that included a diverse variety of adorable pillows designs, patterns, and colours. The main issue that the Syaralise Empire faced was a lack of space to store stock, which caused the operations of checking to slow down.Lack of expertise and insufficient understanding in organizing the products neatly and nicely or information. The syaralise empire also must deal with customer demands from suppliers. This demand exceeded Syaralise Empire's expectations, as it required customized design and the customer was not interested in existing designs. Other than that, the main problem that the Syaralise Empire faced was the pandemic of the Covid-19 attack, which resulted in a decrease in the number of customers using the cash on delivery service as a result of the movement control order action. Last but not least, we will discuss the history of the Syaralise Empire in this case study. Then, we provide our swot analysis and findings regarding the Syaralise empire's problem and how they plan to solve it.